The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1177/15589250231180293
|View full text |Cite
|
Sign up to set email alerts
|

Role of knitted techniques in recent developments of biomedical applications: A review

Abstract: All the surgical bandages, extracorporeal devices, and prosthetic implants that we use today are the product of textiles. Because they conform well to the body and feel good against the skin. Woven, non-woven, and knitted are only textile fabric construction methods. Among all, the knitted structures are more breathable and simpler to produce. In the previous two decades, knitting technology has advanced, now it is simple to create customized flexible and cost-effective biomedical devices. Knitted structures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 87 publications
0
1
0
Order By: Relevance
“…All types of knitted fabrics stem from these foundational structures, which are: single-knit, rib, and interlock [2]. Woven and knit fabrics serve versatile functions across a wide range of industries, including fashion [3], biomedical [4], automotive [5], civil engineering [6,7], and filtration [8].…”
Section: Introductionmentioning
confidence: 99%
“…All types of knitted fabrics stem from these foundational structures, which are: single-knit, rib, and interlock [2]. Woven and knit fabrics serve versatile functions across a wide range of industries, including fashion [3], biomedical [4], automotive [5], civil engineering [6,7], and filtration [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, based on the current overall technological maturity and practical applicability in application areas, along with a comprehensive comparison of several existing technologies, it can be concluded that fiber filtration technology is one of the most widely used technologies at present, among which, air filters are widely used due to their ability to filter and purify particulate matter in the air [ 15 ]. The most commonly used air filtration materials in the current market are mainly melt-blown ultrafine-fiber non-woven fabrics [ 16 ], but the scale of melt-blown fibers is mostly above micrometers, meaning that they cannot effectively intercept tiny, deadly particles in the air. Therefore, the preparation and optimization of fiber materials have always been among the main directions in research on high-performance filtration materials [ 17 ].…”
Section: Introductionmentioning
confidence: 99%